Pedestrian comfort while shopping at the Commercial Nodes of Agra - Jain, Ar. Smriti; Jaiswal, Anuj; Vyas, Supriya (International Journal of Psychosocial Rehabilitation, 2020)
People have a pleasant experience of shopping at places which are walkable. Shopping becomes a whole new experience when a pedestrian feels a sense of comfort. This paper will discuss the pedestrian movement at the commercial nodes in Agra, India. The basic objective of the study is to determine the comfort of pedestrians based on their walking experience while shopping. The commercial node studied is well organised and comes under the Cantonment area of Agra. The pedestrian comfort is kept into mind throughout the years of its renovation. The study inferences indicated that the shoppers were satisfied with the facilities provided for them to make their walking experience comfortable. On a general observation the facilities seemed to be proper and well maintained at most of the locations.